Two‐year, randomized, controlled study of safinamide as add‐on to levodopa in mid to late Parkinson's disease. Issue 10 (10th July 2014) - Borgohain, Rupam; Szasz, Jozsef; Stanzione, Paolo; Meshram, Chandrashekhar; Bhatt, Mohit H.; Chirilineau, Dana; Stocchi, Fabrizio; Lucini, Valentina; Giuliani, Rodolfo; Forrest, Emma; Rice, Patricia; Anand, Ravi; et al.
Abstract In a 6‐month double‐blind, placebo‐controlled study of Parkinson's disease patients with motor fluctuations, safinamide 50 and 100 mg/d significantly increased ON‐time without increasing dyskinesia. Further long‐term safinamide use in these patients was evaluated over an additional 18 months. Patients continued on their randomized placebo, 50, or 100 mg/d safinamide. The primary endpoint was change in Dyskinesia Rating Scale total score during ON‐time over 24 months. Other efficacy endpoints included change in ON‐time without troublesome dyskinesia, changes in individual diary categories, depressive symptoms, and quality of life measures. Change in Dyskinesia Rating Scale was not significantly different in safinamide versus placebo groups, despite decreased mean total Dyskinesia Rating Scale with safinamide compared with an almost unchanged score in placebo. Ad hoc subgroup analysis of moderate to severe dyskinetic patients at baseline (36% of patients) showed a decrease with safinamide 100 mg/d compared with placebo (P = 0.0317). Improvements in motor function, activities of daily living, depressive symptoms, clinical status, and quality of life at 6 months remained significant at 24 months. Adverse events and discontinuation rates were similar with safinamide and placebo. This 2‐year, controlled study of add‐on safinamide in mid‐to‐late Parkinson's disease with motor fluctuations, although not demonstrating an overall difference in dyskinesias between patients and controls, showed improvement in dyskinesia in patients at least moderately dyskinetic at baseline. The study additionally demonstrated significant clinical benefits in ON‐time (without troublesome dyskinesia), OFF‐time, activities of daily living, motor symptoms, quality of life, and symptoms of depression. © 2014 International Parkinson and Movement Disorder Society